Prenatal echocardiographic diagnosis of a discontinuous left pulmonary artery with Taussig–Bing syndrome: a case report and literature review - He, Yun; Yang, Yufei; Song, Xiaoyu; Zhang, Zhonglei; Yan, Dingfang; Xie, Chao; Zeng, Min; Zhang, Wenjun (Frontiers in Pediatrics, 2024)
Background Unilateral pulmonary artery discontinuity (UPAD) is a rare fetal abnormality, for which a prenatal ultrasonographic diagnosis remains challenging. We report a case of left pulmonary artery discontinuity in association with Taussig–Bing syndrome, which has rarely been reported in the literature thus far. Case presentation A pregnant woman with a fetus with congenital heart disease (CHD) at 23 weeks gestation was referred to our center. She denied any familial history of genetic disorders in either spouse, and non-invasive prenatal testing (NIPT) also showed a low risk of CHD for the fetus. An ultrasound examination revealed a complex cardiac malformation indicative of left pulmonary artery discontinuity originating from the ductus arteriosus with Taussig–Bing syndrome. The family eventually chose to terminate the pregnancy and agreed to an autopsy, which confirmed that the prenatal echocardiographic diagnosis was correct. In addition, in this report, we review and analyze 17 reported cases of prenatal echocardiographic diagnoses of UPAD. Conclusions UPAD is characterized by discontinuity between the proximal and distal pulmonary arteries, along with a ductal origin of the distal pulmonary artery. A discontinuous pulmonary artery originating from the ductus can be detected on prenatal sonography using ultrasound technology. The aim is to detect malformations earlier and carry out the necessary intervention measures as soon as possible.